CONCEPT AND ESSENCE OF THE PRINCIPLE OF JUSTICE AS A GENERAL PRINCIPLE OF LAW - Yusuvalieva Rakhima Yusupovna (Modern American Journals, 2025)
The article examines the concept and essence of the principle of justice in law, its various interpretations, the significance of this principle in lawmaking, law enforcement and legal responsibility, legal culture and public relations. The author notes that justice is a complex socio-philosophical category that includes economic, legal, political, moral, social and other aspects of human life. The importance of the principle is that justice as the most important social and cultural value and at the same time as a principle of social structure has an enduring significance for scientific understanding. This category is the subject of scientific research in almost all areas of humanitarian knowledge. The essence of law lies in its focus on achieving justice, eliminating contradictions between people, and ensuring order. The author also dicusses two types of justice: social and legal. In modern legal doctrine, the problems of justice in law are studied both in the theory of law and in branch legal sciences. The article considers different aspects of this principle.
Keywords: Law, justice, legal system, general principles of law, equality, rule of law, civil society.